The effect of modafinil on cognitive function in breast cancer survivors - Sadhna Kohli; Susan G. Fisher; Yolande Tra; M. Jacob Adams; Mark Mapstone; Keith Wesnes; Joseph A. Roscoe; Gary R. Morrow (2009)
Abstract BACKGROUND: The authors conducted a randomized clinical trial examining the effects of modafinil in reducing persistent fatigue in patients after treatment for cancer and performed secondary analyses to assess the effect of modafinil on cognitive function. METHODS: Breast cancer patients who reported a score of ≥2 on the Brief Fatigue Inventory were enrolled in the study. In phase 1 (P1), patients received 200 mg modafinil open‐label once daily for 4 weeks. In phase 2 (P2), patients with a positive response after P1 were randomized either to an additional 4 weeks of modafinil or to placebo. Tests of memory and attention selected from the Cognitive Drug Research (CDR) computerized cognitive assessment were performed at baseline (before modafinil) and after completing phases 1 and 2. The paired differences for each test score were subjected to a Wilcoxon signed rank test. RESULTS: Of the 82 women who were enrolled, 76 completed P1, and 68 completed all assessments in the study. Modafinil had a significant effect on the Speed of Memory ( P = .0073) and Quality of Episodic Memory ( P < .0001) during P1 of the study. After randomization at Week 8, those patients who continued modafinil demonstrated significantly greater improvement in Speed of Memory ( P = .029), Quality of Episodic Memory ( P = .0151), and mean Continuity of Attention ( P = .0101) relative to the group that was switched to placebo. CONCLUSIONS: The authors found that modafinil improved cognitive performance in breast cancer survivors by enhancing some memory and attention skills. Although confirmation is needed, these findings suggest that modafinil may enhance quality of life in this patient population. Cancer 2009. © 2009 American Cancer Society.